INTERNATIONAL TEAM WORK: Analysis of multicultural experiences from managers and students’ perspective. - Uruci, Dajana (My University, 2019)
The theme of cross-cultural has always been the subject of study and examination by many researchers and scholars. Through this thesis, the theme of work in an international team was also added to the cross-cultural theme in order to understand the synergies that can occur between them. This dissertation aims to analyze how multicultural experiences can have an impact on people. Therefore, to the research question, have been added three objectives to make the development of the thesis more efficient. In this case, to answer the research question, it was decided to apply a qualitative analysis, which gives the possibility to interpret the data obtained. As for the interview model, the semi-structured model was chosen. A fundamental role for the analysis of the thesis were the models extensively studied in the chapter dedicated to the theory, such as the model of Hofstede and Trompenaars. Furthermore, the proposed model also played an interesting role as it presented a combination of different variables. As the thesis also considered the interaction of people within teamwork, one of the objectives of the research question was to identify the advantages and disadvantages that emerged from this cooperation. An interesting aspect that offers this dissertation concerns the possibility of investigating the theme through two perspectives: that of managers and that of students. The choice of these two categories is due precisely because these people are often subject to interactions both in teams and against different cultures. In the end, it was concluded by stating that multicultural collaborations are a benefit for people, and this can be seen in detail in the findings.
Keywords: Cross-Cultural, Culture, Team working, Multicultural Team, Advantages, Disadvantages, Manager, Student.; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master's Degree Programme in International Business